Influence of grazing and solar panel installation on tenebrionid beetles (Coleoptera Tenebrionidae) of a central Asian steppe. (15th October 2022) - Tsafack, Noelline; Fang, Wei; Wang, Xingyu; Xie, Yingzhong; Wang, Xinpu; Fattorini, Simone
Abstract: Grazing may represent a major threat to biodiversity in arid grasslands. The increasing use of grasslands for solar parks may represent a new important threat. No study has investigated the effects of solar parks on soil insects. Tenebrionids are a major component of the arthropod fauna of grasslands of central Asia. These ecosystems are threatened by grazing and increasing land use for solar parks. Aim of this work was to investigate the effects of grazing and solar panels on tenebrionids in arid grasslands (desert steppe) in China by comparing their community structure in ungrazed, heavily grazed, and solar park sites. Beetles were sampled by pitfall traps, and sites were compared for abundance and diversity (Hill numbers). All sites were characterized by simple, strongly dominated tenebrionid communities. Species proportions varied among sites. Grazing negatively influenced overall abundance, but did not alter species proportions; by contrast, solar panels had no effect on the average abundance, but reduced the proportion of the most abundant species. Compared with the other two sites, the solar park was characterized by a higher plant biomass and lower temperatures. A major availability of resources and less harsh conditions in the solar park might have a role in reducing the dominance of the most abundant species, allowing other species to attain higher abundances. This led to a more balanced community structure, with higher values of diversity. Although neither grazing nor solar panel installation modified radically tenebrionid species-abundance distribution or diversity, grazing and solar panel installation had different effects in species abundances and their impact might amplify the effect of other disturbance factors such as the ongoing climate change. Graphical abstract: Image 1 Highlights: Grazing is a well-known threat to arid grasslands. Solar parks represent a potential new threat. We investigated their effects on tenebrionids in a Central Asian steppe. Solar park provided more favorable conditions for these beetles. This led to a more balanced community structure, with higher diversity. Grazing affected negatively tenebrionids and is more dangerous than solar park.